Quest HW 6

# Quest HW 6 - roberts(eer474 – Quest HW 6 – seckin...

This preview shows pages 1–2. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: roberts (eer474) – Quest HW 6 – seckin – (56425) 1 This print-out should have 10 questions. Multiple-choice questions may continue on the next column or page – find all choices before answering. 001 10.0 points Find y ′ when xy + 5 x + 3 x 2 = 5 . 1. y ′ = 5 + 3 x- y x 2. y ′ =- y + 5 + 3 x x 3. y ′ =- y + 5 + 6 x x correct 4. y ′ =- ( y + 5 + 6 x ) 5. y ′ = y + 5 + 6 x x 6. y ′ = y + 5 + 3 x x Explanation: Differentiating implicitly with respect to x we see that d dx ( xy + 5 x + 3 x 2 ) = d dx (5) . Thus ( xy ′ + y ) + 5 + 6 x = 0 , and so xy ′ =- y- 5- 6 x . Consequently, y ′ =- y + 5 + 6 x x . 002 10.0 points Find dy dx when 4 √ x + 5 √ y = 7 . 1. dy dx = 4 5 ( xy ) 1 / 2 2. dy dx = 4 5 parenleftBig y x parenrightBig 3 / 2 3. dy dx =- 5 4 parenleftBig x y parenrightBig 3 / 2 4. dy dx = 5 4 ( xy ) 1 / 2 5. dy dx =- 4 5 parenleftBig y x parenrightBig 3 / 2 correct 6. dy dx = 5 4 parenleftBig x y parenrightBig 3 / 2 Explanation: Differentiating implicitly with respect to x , we see that- 1 2 parenleftBig 4 x √ x + 5 y √ y dy dx parenrightBig = 0 . Consequently, dy dx =- 4 5 parenleftBig y x parenrightBig 3 / 2 ....
View Full Document

{[ snackBarMessage ]}

### Page1 / 5

Quest HW 6 - roberts(eer474 – Quest HW 6 – seckin...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online